1986
DOI: 10.1073/pnas.83.18.7044
|View full text |Cite
|
Sign up to set email alerts
|

Glycoconjugates as noninvasive probes of intrahepatic metabolism: pathways of glucose entry into compartmentalized hepatic UDP-glucose pools during glycogen accumulation.

Abstract: Recent studies have questioned the efficiency with which administered glucose generates hepatic glycogen through the direct nonrecycling route compared with the indirect route from glucose recycled through glycolysis followed by gluconeogenesis. Using fasted and refed rats, we examined the relative access of infused (l-3H]-and [U-'4Cjglucose by way of these two pathways to liver glycogen and to hepatic glucuronic acid, the latter recovered from the urine as the glucuronide conjugated with administered acetamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…Weight did not change and participants were instructed to maintain their habitual diet and exercise regimens during the study, suggesting that the increase in EGP seen in the placebo group represents the natural disease progression. In addition, increased fasting glucose clearance with colesevelam treatment could reflect direct uptake of glucose by the liver for storage in glycogen (the direct pathway [38,39]), which in turn could account for the apparent stabilisation of hepatic glycogenolysis. The significance of this stabilising effect of colesevelam on EGP and glycogenolysis must be interpreted with caution because the treatment effect did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Weight did not change and participants were instructed to maintain their habitual diet and exercise regimens during the study, suggesting that the increase in EGP seen in the placebo group represents the natural disease progression. In addition, increased fasting glucose clearance with colesevelam treatment could reflect direct uptake of glucose by the liver for storage in glycogen (the direct pathway [38,39]), which in turn could account for the apparent stabilisation of hepatic glycogenolysis. The significance of this stabilising effect of colesevelam on EGP and glycogenolysis must be interpreted with caution because the treatment effect did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Magnusson et al (1987) reported that glucuronide formation could be used to represent the hepatic uridine diphosphate-glucose pool that is the precursor of glycogen formation, but Hellerstein et al (1986) reported that the glucuronide could not be used because it was representative of a different pool. Re-interpretation of the data of Hellerstein et al (1986) supported the conclusion of Magnusson et al (1987). The glucuronide has been used to trace glycogen formation since that time.…”
Section: Mass-isotopomer-distribution Analysismentioning
confidence: 99%
“…The technique for placement and maintenance of indwelling intrajugular silastic catheters has been described elsewhere (25). Catheterization may depress food intake for 24-48 h, therefore no studies were performed for at least 72-96 h after catheter placement, until food intake had stabilized at precatheterization values.…”
Section: Methodsmentioning
confidence: 99%